2005
DOI: 10.1213/01.ane.0000153013.34129.a7
|View full text |Cite
|
Sign up to set email alerts
|

Oral Herpes Simplex Reactivation After Intrathecal Morphine: A Prospective Randomized Trial in an Obstetric Population

Abstract: There is now evidence for an association between the use of epidural morphine and reactivation of herpes simplex labialis (HSL). There are no studies that definitively demonstrate the relationship between HSL reactivation and spinal intrathecal morphine. To investigate this relationship, we randomized and prospectively studied 100 obstetric patients with a history of HSL undergoing cesarean delivery under spinal anesthesia. One group received intrathecal morphine plus IV morphine via patient-controlled analges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Opiates have been found to have many physiological and immunological effects that influence the pathogenesis of infectious diseases (17). In humans, it has been reported that morphine administration induces reactivation of latent herpes simplex labialis (8). In this paper we showed that acute morphine administration, similarly to hyperthermic stress, reduces CTL responses, lymphocyte proliferation, and IFN- production and induces reactivation of latent HSV-1 in a mouse model.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Opiates have been found to have many physiological and immunological effects that influence the pathogenesis of infectious diseases (17). In humans, it has been reported that morphine administration induces reactivation of latent herpes simplex labialis (8). In this paper we showed that acute morphine administration, similarly to hyperthermic stress, reduces CTL responses, lymphocyte proliferation, and IFN- production and induces reactivation of latent HSV-1 in a mouse model.…”
Section: Discussionmentioning
confidence: 64%
“…Our previous work has shown that acute morphine administration increases mortality during HSV-1 infection in BALB/c mice (7). In humans, morphine administration induces reactivation of latent herpes simplex labialis (8). Recurrent HSV-1 ocular disease results from reactivation of the latent virus in the trigeminal ganglia, often following immunosuppression or exposure to a variety of psychological or physical stressors.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify whether intrathecal morphine specifically increased the risk of reactivation versus systemic opioids, Davies et al 30 designed a randomized controlled trial that included women with a reported history of HSV-1 scheduled for elective cesarean delivery under spinal anesthesia. This trial confirmed an increased risk of reactivation with intrathecal morphine.…”
Section: Hsv Reactivation After Neuraxial Morphine For Cesarean Delivmentioning
confidence: 99%
“…However, clinicians are understandably concerned about the risk of HSV transmission to the neonate whose mother has a recurrence. 27,28,30 …”
Section: Hsv Reactivation After Neuraxial Morphine For Cesarean Delivmentioning
confidence: 99%
“…Consistent with these findings, opioid administration has been associated with increased susceptibility of animals to microbial infection [15] . It has been proven that morphine alters the course of HSV-1 infection [16,17] . Furthermore, morphine reduces the activity of immune cells, including NK cells and macrophages, and decreases the production of cytokines like IFN-␥ and IL-12 [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%